Female Medical Students’ Relationship Styles And Their Intended Primary Care and Non-Primary Care Postgraduate Specialty Preferences - Memon, Shabnam Iqbal; Shaikh, Sirajul Haque (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the predominant relationship/attachment styles of final year female medical students of a Pakistani medical college with their intended primary care and non-primary care post-graduate speciality preferences.Study Design: Cross-sectional comparative study.Place and Duration of Study: Sir Syed College of Medical Sciences for Girls, Karachi, from Feb to Apr 2019.Methodology: Final year MBBS students were included in the study. Students were asked to complete a validated relationship scales questionnaire to determine the dominant relationship/attachment style. Students were also asked to identify their intended first choice for post-graduate specialization from a list of 28 primary care and non-primary care post-graduate specialities.Results: Out of 113 female students, 48 (43%) were found to have a predominantly dismissing relationship style (among four variants of relationship styles). Out of 95 (84%) students opted for a non-primary care speciality for pursuing post-graduation, out of which 37 (33%) students chose Obstetrics and Gynaecology. Comparison of participant’s relationship styles with postgraduate speciality showed no significant difference (p-value=0.40).Conclusion: Medical students should be provided adequate and timely exposure to various specialities available for postgraduation (primary and non-primary care specialities) and should be guided appropriately to help them make informed career choices.